STUDY ON DIRECT MEDICAL COSTS IN THE TREATMENT OF ACUTE ISCHEMIC STROKE WITH ALTEPLASE AT BINH DUONG PROVINCIAL GENERAL HOSPITAL IN 2024-2025 - Than, Thi Thao Nhi; Nguyen, Trung Kien; Nguyen, Van Tinh (Cantho Journal of Medicine and Pharmacy, 2025)
Background: Stroke is considered the third leading cause of death after cardiovascular diseases and cancer. International studies indicate that the total cost of stroke treatment in developed nations, such as the United Kingdom, amounts to £8.97 billion annually, with direct medical costs accounting for up to 49%. Researching direct medical costs not only helps manage and utilize healthcare resources efficiently but also provides valuable information for healthcare facilities in policy-making and improving the quality of care. Therefore, we are conducting the study to contribute to the development of an appropriate healthcare cost model, thereby alleviating the burden on patients and the healthcare system in the future. Objective: To determine the direct medical costs of ischemic stroke treatment using Alteplase at Binh Duong General Hospital in the period of 2024–2025. Materials and methods: A cross-sectional descriptive study on 30 patients treated for acute ischemic stroke with Alteplase at Binh Duong Provincial General Hospital from May 2024 to January 2025. Results: The direct medical cost for the treatment of ischemic stroke with Alteplase was 22,538.51 (IQR = 9,165.2) thousand VND. The cost of medication accounted for the highest proportion at 59.7%. The difference in direct medical costs for the treatment of ischemic stroke with Alteplase between age groups, length of treatment, and treatment outcomes according to NIHSS at 24 hours was statistically significant (p < 0.05). Conclusions: The direct medical cost for the treatment of ischemic stroke with Alteplase was 22,538.51 (IQR = 9,165.2) thousand VND.